Analisis Pelaksanaan Rekrutmen Calon Kepala Sekolah Dasar Dan Sekolah Menengah Pertama Di Dinas Pendidikan Dan Kebudayaan Kabupaten Ogan Ilir - Sayadi, Sayadi; Idi, Abdullah; Mardianto, Mardianto (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
Analysis The implementation of the recruitment of prospective school principals that has been carried out at the Ogan Ilir District Education and Culture Office is an innovation in an educational institution to recruit professional principals and will produce competent prospective principals who will be able to develop and empower themselves and will spur increased principal performance. the schools he leads towards improving the quality, relevance and competitiveness of education. This research is a descriptive research with a qualitative approach. The theory used in this research is George Terry's Management Function Theory (2010: 9) which consists of four dimensions of Planning, Organizing, Implementation and Monitoring of Research Results, some of which have gone well and some that have not gone well, one of which is the preparation of the recruitment program namely through the operational guidelines and technical guidelines to recommend prospective school principals to be selected by proposing prospective principals to be carried out by the school supervisor then the names of the prospective principals are sent to the Office of the Education Office, but unfortunately the recruitment of prospective principals is still lacking. and Junior High Schools in the Ogan Ilir Regency Education and Culture Office which are not in accordance with the SOPs set by the National Education Office so that the recruitment process for administrative selection and academic selection for prospective school principals has not been carried out properly.